Ecuador : Country Financial Accountability Assessment - World Bank (Washington, DC, 2012)
Despite positive economic signals in 2002 and 2003, Ecuador's public finances remain precarious because of weaknesses in government systems and oversight for the non-financial public sector and dependence on volatile fiscal revenue from oil. More than 96 percent of total public expenditure is fixed (public sector wages and salaries, social security benefits, debt service, and other contractual arrangements), reducing the scope for discretionary spending. The strategic objective of the present CFAA is to contribute to strengthening of Ecuador's economic governance, and associated social and economic development, identifying weaknesses and recommending remedial action in areas where current public financial management institutional arrangements, practices and systems, limit the efficiency and transparency of public sector management. This being the first CFAA for Ecuador, the study reviewed the practices and systems of the Central administration of Government. The report's main recommendations include consolidating existing laws and regulations on public financial management and modernizing the legal framework; preparing and implementing supporting regulations on budget management and performance, and enhancing civil society's capacity to scrutinize public finances; upgrading information systems; improving operational procedures; designing and implementing a capacity building program to upgrade the accounting framework; elaborating a borrowing policy and developing procedural manuals; strengthening internal audit units; strengthen the Supreme Audit Institution; improve legislative scrutiny of government spending; upgrade the Government's Internet portal, and provide more user-friendly access to information on budget execution and financial performance.